Iowa CBC reporting form, Cedar Falls, December 22, 1985 - Moore, Francis L.et al (1985)
Checklist dated December 22, 1985 compiled by Francis Moore. A list of birds sighted by Moore and four others around Cedar Falls. A total of 55 species and 6,963 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed